Verificação do impacto de uma sequência didática sobre processos energéticos celulares para potencialização da transferência da aprendizagem na educação básica - Heverton Pires Souza (2022)
In High School, students are required to show a high level of abstraction in order to study the myriad of metabolic processes associated with structures and cellular organization. In addition to the little to no time available to discuss the whole Biochemistry content, students fail to recognize the existence of a reality invisible to the eye, increasing their challenge to interact with the microscopic and submicroscopic worlds which hampers their learning of Biochemistry. Therefore, the present study was carried out through the development of a didactic sequence on cellular energetic processes as a way to enhance the transfer of learning of students. In this sense, the strategies were associated with six stages of the students' learning process: motivating, stimulating, knowing, reacting, re-feeding and memorizing. In this context, the didactic sequence was identified in six stages of development: (i) building word clouds according to the students' previous knowledge; (ii) chatting circle of students based on problems with the concepts of life and energy; (iii) explanation of cellular energetic processes; (iv) processes generated through problematization related to energy processes; (v) verification of the transfer of learning through the creation of parodies, development of concept maps and application of games; and (vi) evaluation of the proposal. Thirty students of the 2nd Year of High School from Escola Estadual Doutor Odilon Loures were involved in this research. The application of the didactic sequence led the students to develop the construction of critical thinking. As a result of this study, a manual of practices was written so that it can be used by other teachers to develop the theme.